International Legal Responsibility of International Organizations in the ILC Draft Articles and Beyond - Bayani, Sarah (Universitätsverlag Göttingen, 2022)
The phenomenon of proliferation of international organizations has urged focus on the responsibility of international organizations under international law as the effect of their activities is witnessed everywhere in our daily life. The main purpose of the present book is to examine and review some specific aspects relevant to the question of international legal responsibility of international organizations, mainly, with a view to assessing the International Law Commission's work on the codification of the international legal rules applicable on international organizations in this area. At the same time, the intention is to address the major challenge to the codification of general rules for international organizations, namely, their wide-varying nature and their differences from each other. Furthermore, the perspective has been enlarged by elaborating on the broader concept of accountability of international organizations.